The Role Of Entrepreneurship In Driving Sustainable Economic Development In Uzbekistan - Оzоdjоn Shаvkаt ugli Musаev (Periodica Journal, 2025)
Entrepreneurship has become a key driver of economic transformation in emerging economies. In Uzbekistan, recent reforms and policy measures have created a favorable environment for entrepreneurs. This paper explores how entrepreneurship contributes to sustainable economic development in Uzbekistan by analyzing its social and economic impact, the government’s role, and ongoing challenges. The findings suggest that entrepreneurship is a vital mechanism for innovation, employment generation, and inclusive growth.
Keywords: entreрreneurshiр; smаll business; sociаl entreрreneurshiр